2004
DOI: 10.1289/ehp.7022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,3-Butadiene, Isoprene, and Their Photochemical Degradation Products on Human Lung Cells

Abstract: Because of potential exposure both in the workplace and from ambient air, the known carcinogen 1,3-butadiene (BD) is considered a priority hazardous air pollutant. BD and its 2-methyl analog, isoprene (ISO), are chemically similar but have very different toxicities, with ISO showing no significant carcinogenesis. Once released into the atmosphere, reactions with species induced by sunlight and nitrogen oxides convert BD and ISO into several photochemical reaction products. In this study, we determined the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 41 publications
5
73
0
Order By: Relevance
“…Previous in vitro studies using a gasphase-only exposure system have shown that gas-phase products of isoprene photooxidation significantly enhance cytotoxicity and IL-8 expression (Doyle et al, 2004(Doyle et al, , 2007.…”
Section: Biological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies using a gasphase-only exposure system have shown that gas-phase products of isoprene photooxidation significantly enhance cytotoxicity and IL-8 expression (Doyle et al, 2004(Doyle et al, , 2007.…”
Section: Biological Implicationsmentioning
confidence: 99%
“…In this study we chose to examine the gene expression levels of interleukin-8 (IL-8) and cyclooxygenase-2 (COX-2), not only for their links to inflammation and oxidative stress (Kunkel et al, 1991;Uchida, 2008) but also because both have been examined in previous studies using the EAVES for fresh and aged diesel exhaust (Lichtveld et al, 2012). Other studies on air pollution mixtures have also examined IL-8 as a biological endpoint due to its involvement with inflammation (Zavala et al, 2014;Ebersviller et al, 2012a, b;Doyle et al, 2004Doyle et al, , 2007. We compared the gene expression levels in cells exposed to SOA generated in an outdoor chamber from photochemical oxidation of isoprene in the presence of NO and acidified sulfate seed aerosol to cells exposed to a dark control mixture of isoprene, NO, and acidified sulfate seed aerosol to isolate the effects of the isoprene-derived SOA on the cells using the EAVES.…”
mentioning
confidence: 99%
“…Results also suggested that there were even more unmeasured products contributing to the toxicity but these were detected toxicologically. [68,69] In addition, traditional photo-irradiation experiments of 1,3-butadiene and NO x were conducted and modelled to show that these experiments were useful for both chemical mechanism testing as well as toxicity testing, and gave validity to the realism of the exposure conditions for the toxicity testing. [70] Meanwhile, the new chamber and laboratory were constructed (Fig.…”
Section: Expansion Of the Research Group And Chambers To Test Combustmentioning
confidence: 99%
“…A549 human respiratory cells are a commercially available cell line that have been shown to react in a manner that is representative of the human airway in vivo (Lieber et al, 1976;ATCC, 2011). The A549 cells were cultured and prepared for exposure as explained previously (Jaspers et al, 1997;Doyle et al, 2004;Sexton et al, 2004;de Bruijne et al, 2009;Ebersviller et al, 2012a). The Gas In Vitro Exposure System (GIVES) and Electrostatic Aerosol in Vitro Exposure System (EAVES) have also been described in detail previously (Ebersviller et al, 2012a;Lichtveld et al, 2012;de Bruijne et al, 2009;Doyle et al, 2004Doyle et al, , 2007Sexton et al, 2004).…”
Section: Biological Effects Model and Measurements Of Responsementioning
confidence: 99%
“…Previous experiments using outdoor irradiation chambers have measured significant changes in chemical composition as air pollution mixtures age in sunlight and, in most cases, have measured an accompanying increase in toxicity. In addition, these studies have indicated that the overall toxicity of an aged pollution mixture may not be completely accounted for by the major daughter products alone, and that significant portions of the observed response can be induced by exposure to minor, and even undetected, products Doyle et al, 2004Doyle et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%